Three-dimensional uniaxially aligned nanofibre construct using secondary electrode assisted gap electrospinning - A. H., Nurfaizey (Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at http://ijneam.unimap.edu.my